Close up: The female gaze and ethnic difference in two Vietnamese women's films. (14th September 2015) - Duong, Lan
Abstract : This article looks at two contemporary films by Vietnamese women. In Việt Linh's Travelling Circus (1988) and Phạm Nhuệ Giang's The Deserted Valley (2002), a female gaze is sutured to that of an ethnic minority character's, a form of looking that stresses a shared oppression between women and the ethnic Other. While clearing a space for a desiring female gaze in Vietnamese film, they nonetheless extend an Orientalist view of racialised difference. A feminist film optic, one that does not consider industry history and constructions of race, fails to mark out the layered relations of looking underlying Vietnamese filmmaking. This study attends to the ways women filmmakers investigate gendered forms of looking, sexual desire and otherness within the constraints of a highly male-dominated film industry.